Transcutaneous oxygen pressure (TcPO2) and ulcer outcome in diabetic patients: Is there any correlation?. Issue 2 (March 2019) - Zubair, Mohammad; Ahmad, Jamal
Abstract: Background: Due to poor blood circulation, the prevalence of foot ulcer is extensively reported among diabetic patients. Diabetic neuropathy is the critical factor of diabetes that can affect the nerves. Objective: To examine the outcomes and correlation between TcPO2 and ulcer outcomes among diabetic patients. Material and methods: A prospective cohort design has been employed to compare and correlate TcPO2 group with ulcer outcomes. A total of 192 patients were enrolled, who underwent diagnosis for ulcer outcome. Descriptive analysis and Pearson Correlation were used for data analysis via SPSS version 20. Results: The prevalence of minor amputation among diabetic patients in 25–40 mmHg 75 (85.22%) and >40 mmhG 73 (84.88%) group is reported for ulcer outcome. Mostly diabetic patients were healed with intact skin (male = 36, female = 73), and improved ulcer healing (male = 23, female = 43). Correlation between ulcer size (p = .016), ABI (p = .044), TBI (p = .000), Adiponectin (p = .009), HbA1c (p = .033), and S. creatinine (p = .025) was significant with TcpO2 group. Conclusions: The study concluded that there is a positive and significant correlation between TcPO2 group and ulcer outcome. There is a positive association between TcPO2 baseline and degree of ulcer healing with intact skin.